2018
DOI: 10.1038/s41419-017-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

YAP triggers the Wnt/β-catenin signalling pathway and promotes enterocyte self-renewal, regeneration and tumorigenesis after DSS-induced injury

Abstract: Impaired epithelial regeneration is a crucial pathophysiological feature of ulcerative colitis (UC). Yes-associated protein (YAP1) appears to control cell proliferation and differentiation. In this study, we sought to identify the roles of YAP in intestinal epithelial cell (IEC) self-renewal, regeneration and tumorigenesis. We first observed that YAP was significantly reduced in 62.5% (45/72) of human UC tissues and it was dramatically enhanced during epithelial regeneration in a murine colitis model. Using le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 47 publications
6
130
0
2
Order By: Relevance
“…There is emerging evidence that physiological Hippo signaling is not only important for anti-pathogenic immunity but also might serve to link the activation and resolution phases of an immune response. In the context of tissue injury, Hippo signaling may be differentially regulated by multiple inputs, including contact inhibition, mechanotransduction and inflammatory mediators [ 61 ]. In their description of Yki-induced Upd3 expression, Houtz et al showed that Yki and Scalloped function within a Misshapen (Msn)-Wts-Yorkie/Scalloped-Upd3 signaling axis that enhances intestinal tissue renewal during the Drosophila midgut response to Ecc15 bacterial infection [ 55 ].…”
Section: Hippo Signaling Is Part Of An Immune Responsementioning
confidence: 99%
“…There is emerging evidence that physiological Hippo signaling is not only important for anti-pathogenic immunity but also might serve to link the activation and resolution phases of an immune response. In the context of tissue injury, Hippo signaling may be differentially regulated by multiple inputs, including contact inhibition, mechanotransduction and inflammatory mediators [ 61 ]. In their description of Yki-induced Upd3 expression, Houtz et al showed that Yki and Scalloped function within a Misshapen (Msn)-Wts-Yorkie/Scalloped-Upd3 signaling axis that enhances intestinal tissue renewal during the Drosophila midgut response to Ecc15 bacterial infection [ 55 ].…”
Section: Hippo Signaling Is Part Of An Immune Responsementioning
confidence: 99%
“…Recently, the Hippo pathway has been reported to be connected to Wnt/β-catenin signaling. The Hippo signal transducer YAP/TAZ is part of the β-catenin disruption complex, which can coordinate the Wnt/β-catenin response regulating stem cell self-renewal and tissue homeostasis ( Deng et al, 2018 ). In cancer cells, the downregulation of Hippo signaling is linked to the upregulation of β-catenin activity.…”
Section: The Wnt/β-catenin Signaling Pathway and The Hippo Signaling mentioning
confidence: 99%
“…YAP and TAZ can also reduce sensitivity to DNA damaging agents by upregulating signaling which bypass cell cycle checkpoints induced by DNA damage, or by upregulating pro-survival and pro-proliferative signaling, typically hyperactivated in cells with stemness properties, where YAP/TAZ are often overexpressed and whose number increases over the course of radiotherapy and chemotherapy to repopulate the tumor mass [ 208 ]. It has also been shown that hyperactivation of β-catenin signaling can increase chemoresistance and radioresistance in different cancer types [ 209 , 210 , 211 ], and a synergism between β-catenin and YAP/TAZ has been described in cancer, including lung cancer [ 64 , 212 , 213 , 214 ], suggesting a possible role of YAP and TAZ in chemoresistance and radioresistance through its crosstalk with β-catenin signaling that needs to be further investigated in lung cancer. All the mechanisms described above can explain how cancer cells overexpressing YAP and/or TAZ can bypass the inhibitory effect of cytotoxic chemotherapy and radiotherapy.…”
Section: Synergism Between Yap/taz Inhibition and Current Therapiementioning
confidence: 99%